The Power of the Force: Mechano-Physiology of the Giant Titin - (:unkn) unknown (PORTLAND PRESS LTD, 2018)
Titin - the largest protein in the human body - spans half of the muscle sarcomere from the Z-disk to the M-band through a single polypeptide chain. More than 30 000 amino acid residues coded from a single gene (TTN, in humans Q8WZ42) form a long filamentous protein organized in individual globular domains concatenated in tandem. Owing to its location and close interaction with the other muscle filaments, titin is considered the third filament of muscle, after the thick-myosin and the thin-actin filaments.